2011
DOI: 10.1097/pcc.0b013e3181e30d09
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell transfusion in critically ill children: A narrative review*

Abstract: The available evidence does not support the extensive use of RBC transfusions in general or critically ill patients. Transfusions are still associated with risks, and although their benefits are established in limited situations, the associated negative outcomes in many more patients must be closely addressed. Given the frequency of anemia and its proven negative outcomes, transfusion decisions in the critically ill children should be based on individual patient's characteristics rather than generalized trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 117 publications
1
32
0
9
Order By: Relevance
“…[3] It is therefore important to ensure patient safety by developing, implementing and regulating blood transfusion protocols. Research performed over the past decade has shown that the pretransfusion haemoglobin (Hb)/haematocrit (Hct) threshold could be related to adverse outcomes.…”
Section: Researchmentioning
confidence: 99%
“…[3] It is therefore important to ensure patient safety by developing, implementing and regulating blood transfusion protocols. Research performed over the past decade has shown that the pretransfusion haemoglobin (Hb)/haematocrit (Hct) threshold could be related to adverse outcomes.…”
Section: Researchmentioning
confidence: 99%
“…RBCTs have been recognized to pose risks associated with storage and in relation to the immunomodulatory effects that occur in almost all recipients; this underlines a possible association between RBCT and higher mortality and nosocomial infection rates. [2][3][4] Recognizing these risks has resulted in a more critical approach to the benefits associated with RBCT. The underlying mechanisms of immune response modulation by RBCT may include biological response modifiers of white blood cells, impaired T cell and natural killer cell activity, and defects in antigen presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Exsanguination, either at the site of the accident, or in hospital, accounts for 45% of all traumatic deaths. Motor vehicle collisions (59% mortality from all accidents in age group [5][6][7][8][9][10][11][12][13][14], pedestrian and bicycle accidents, falls, burns, and physical assault are the most common causes of injury in children (1). Many of injured children will require surgical treatment with involvement of the anesthesiologist.…”
Section: Introductionmentioning
confidence: 99%